2013
DOI: 10.1111/imj.12108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in patients referred with snoring and obstructive sleep apnoea

Abstract: Depending on classification, 32-53% of patients with snoring had depressive symptoms or were on treatment, which is significantly greater than the Australian average of 21%. A simplified depression questionnaire was validated. Severity of depression correlated with sleepiness and hypoxaemia but not with severity of sleep apnoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
1
30
2
Order By: Relevance
“…In that study, the prevalence of depression assessed with the MINI questions was 45% and a significant correlation was reported (0.736; p < 0.001) between HADS and the MINI depression questions. 32 This is a much higher prevalence of depression than reported in our study but the fact that Douglas et al 32 only used two screening questions from the MINI has to be considered a limitation and could partially explain the difference in the results. Another recent study indicated that HADS would be an accurate screening tool for assessing major depression among patients in sleep disorder clinics 33 but further studies comparing the use of self-report questionnaires and structured clinical interviews in large cohorts of patients with OSA are needed.…”
Section: Table 4-predictivecontrasting
confidence: 53%
See 1 more Smart Citation
“…In that study, the prevalence of depression assessed with the MINI questions was 45% and a significant correlation was reported (0.736; p < 0.001) between HADS and the MINI depression questions. 32 This is a much higher prevalence of depression than reported in our study but the fact that Douglas et al 32 only used two screening questions from the MINI has to be considered a limitation and could partially explain the difference in the results. Another recent study indicated that HADS would be an accurate screening tool for assessing major depression among patients in sleep disorder clinics 33 but further studies comparing the use of self-report questionnaires and structured clinical interviews in large cohorts of patients with OSA are needed.…”
Section: Table 4-predictivecontrasting
confidence: 53%
“…An Australian study by Douglas et al 32 showed that among patients with suspected OSA, the overall rate of depression based on doctor diagnosis, Hospital Anxiety and Depression Scale (HADS), or two screening questions from the MINI was 53%. In that study, the prevalence of depression assessed with the MINI questions was 45% and a significant correlation was reported (0.736; p < 0.001) between HADS and the MINI depression questions.…”
Section: Table 4-predictivementioning
confidence: 99%
“…5,7 This study provides further evidence for this association, suggesting substantial potential for diagnostic confusion between the entities. It improves on previous studies by: investigating a relatively large number of participants; characterizing OSA presence and severity using gold standard laboratory polysomnography; assessing depressive symptoms prospectively using a well validated screening tool; accounting for potential age and obesity confounding; assessing the influence of gender on this relationship; and by determining the efficacy of CPAP treatment on depressive symptomatology using an objective method (device recorded hours of use) to assess compliance.…”
Section: Depressive Symptoms Are Common Among People With Osamentioning
confidence: 58%
“…3,5,6 Many previous studies have been of low power or have used a variety of instruments of varying quality to assess depressive symptoms. 6 Lack of direct contact with patients and retrospective assessment of depressive symptoms rather than assessment prior to diagnosis of OSA have been limitations of some of them.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…Patients with depression are often referred to sleep laboratories with complaints of insomnia or, less frequently, with unusually long sleep of low quality (5). Some clinical rating scales for depression focus on fatigue and tiredness rather than EDS, and a potential association between …”
Section: Mood and Sleepinessmentioning
confidence: 99%